Application of Character Values for Teenage Proletarians at the North Jakarta Kemah Kasih Foundation - Sutrisno, Sutrisno; Repi, Robby Robert; Halawa, Maju (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2022)
The community service activities carried out aimed at improving the values of the character of the proletariat of adolescents (12-17 of ages) in the Yayasan Kemah Kasih so that they become a better person and can be accepted by the community well. Counseling conducted in this activity is to provide assistance and understanding about the application of character values that must be possessed by proletariat teenagers (12-17 of ages). The result of this community service activity is that the counseling conducted effectively can improve the understanding and ability of proletariat youth (12-17 of ages) regarding values in character education such as respecting diversity, understanding the shortcomings and advantages of themselves, showing self-confidence, independence, obeying the social rules that apply in the environment and instilling moral values they can apply in social life.